Comparative analysis of organizationalculture transformation models - I. V. Groshev; Menin He (Управление)
An analysis of organizational culture transformation models has been presented. The mechanisms and tools which can be used for changes, have been studied, which are understood as any actions aimed at reviving or reorienting the activity of the organization. Cultural changes in the form of a matrix, containing the effects of reactive and proactive factors and ameliorative and strategic goals, have been analysed.Correlations between the stage of development of organizational culture and its transformation have been highlighted. Depending on the stage reached by the organization, specific sets of measures specific sets of measures are being taken. The key elements that can ensure the success of organizational and cultural changes, such as leadership, staff involvement, stakeholder participation, communication changes, emotion management, etc., have been considered. Four main sources of change have been determined, three of which are relatively independent of management actions, and the fourth is directly related to management actions: survival, evolutionary, revolutionary processes, and managed changes. In the process of cultural change, three main stages in the life of an organization have been emphasized: the foundation and early growth, development, maturity and decline, and the corresponding mechanisms and tools of organizational culture, which can be used for change. In particular, the following have been reviewed in detail: gradual change; changing organizational “therapy”; developing elements of mixed culture; selectively promoting subcultures; planning for project development and creating a structure for the organization; defrosting and changing through new technologies; changing by infusing personnel from outside the organization; defrosting conflicts and challenging myths; basic remodeling of the organization; change by compulsion.The limitations that arise in the process of organizational culture transformation have been analysed. It has been concluded that regardless of which model will be adopted as the basis for the process of changing the organizational culture, the context in which the transformations take place should be taken into account. The enabling conditions, facilitating transformation and the reactive factors, that will resist it, should be understood and analysed by decision-makers.